Membangun Moderasi Beragama di Ruang Digital: Strategi Dakwah Berbasis Parodi pada Kanal YouTube Ustaz Ammi Nur Baits - Hapsako, Catur Baro; Hamidah, Lilik; Arif, Moch. Choirul (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to analyze the messages of creed (aqidah) and religious moderation in the YouTube content "Bareng Mas Mitro" on the ANB Channel, using Roland Barthes' semiotic analysis. The methodology used is descriptive qualitative, which dissects visual and verbal signs to find denotative and connotative meanings. The background of this research is the phenomenon of digital da'wah facing challenges such as the spread of deviant teachings and radicalism, as well as the prevalence of mystical practices like the use of amulets that contradict the principle of tauhid (monotheism), particularly among the younger generation. The results show that Ustaz Ammi Nur Baits and the ANB Channel team succeeded in conveying da'wah messages that rectify the understanding of aqidah and religious moderation through a light and entertaining approach. The semiotic analysis of the "Jimat Penglaris" episode debunks the myth that amulets have spiritual power, confirming that such practices are a form of deception that can damage one's creed. The novelty of this research lies in its analysis of the da'wah messages of a Salafi "da'i influencer," who blends aqidah and religious moderation with Javanese local wisdom in an entertaining parody format. This approach demonstrates the effectiveness of digital da'wah in reaching a lay audience in a rational and contextual manner, while also correcting common misconceptions in society.